Predicting homozygous M694V genotype in paediatric FMF: multicentre analysis and scoring system proposal - Tunce, Eray; Atamyildiz Ucar, Sila; Polat, Merve Cansu; Altug Gucenmez, Ozge; Cakan, Mustafa; Bozkaya Yucel, Burcu; Soezeri, Betuel (Oxford Univ Press, 2025)
Objectives: This study aimed to evaluate the predictability of the homozygous M694V genotype in paediatric FMF patients and to develop a clinical scoring system to enhance disease management strategies. Methods: This nationwide, multicentre, cross-sectional study included 3981 paediatric FMF patients with biallelic pathogenic variants in exon 10 of the Mediterranean fever gene. Patients were divided into two groups: group 1 (homozygous M694V) and group 2 (other variants). Data were collected from 37 paediatric rheumatology and/or nephrology clinics across T & uuml;rkiye, covering patients followed between 2014 and 2023. Results: Group 1 had significantly earlier symptom onset (<= 3 years: 49.8% vs 43.9%, P < 0.001) and diagnosis (median age: 5 years vs 5.8 years, P < 0.001) compared with group 2. A higher prevalence of family history of FMF was observed in group 1 (P < 0.001). Clinical manifestations, including arthritis (27.5%), erysipelas-like erythema (ELE) (20.3%) and protracted febrile myalgia syndrome (PFMS) (3.6%), were significantly more frequent in group 1 (P < 0.001 for all). Colchicine resistance was also higher in group 1 (18.1% vs 5.1%, P < 0.001). Logistic regression analysis showed that <= 3 years of age at symptom onset, family history, arthritis, myalgia, PFMS, ELE and splenomegaly were independent predictors of the homozygous M694V genotype. A clinical scoring system was proposed based on these findings. Conclusion: This study provides valuable insights into the clinical predictors of the homozygous M694V genotype in paediatric FMF. The proposed scoring system will support clinicians in prognosis assessment and treatment planning, contributing to improved patient outcomes.
Keywords: FMF; genotype; M694V; paediatric; phenotype; predictability; scoring system